Programa saúde da família: modalidade de conhecimento socialmente elaborado - Almeida, Maria Irismar de (2001)
The study lias as objectives to understand the social representations elaboraled by nurses, health practices in PSF field from the social representations idcmtified. The study took place in a Municipal of seaside, located far 29 km of Fortaleza with nine nurses, ílfty four agents and seventy-five women of the community, The collcciton of data was accomplished in vífits to the bafic units of health in lhe headquarters, rural and familiar areas selected ufmg the direct observation, the semi-structured interview and technician-normative documents. The data collected were submitted to content analysis technique, from which come up these categories: knowledge about Program of Family Health; profissional practices in PSF; expectations, reivindications and possibilíties in relation to ProgranTs continuity. The results reveald knowledge socially elaborated by nurses, healtlfs agents and families about lhe program of Health Family, with understandings favorablc, representing it as a way to suffering’s, reduction, favo uri ng a communication more effective from the work done In team capable to consider their reivindications5’. As desfavorable understadings, the social subjects represented by “preocupations in achieve goals and ambulatorial Service. This rneans a famess among what the governors talk and the daily life of research’s subjects. Thus, it was observed that the continuity of the Program is only possible, with the promisement of municipal, State and federal ruler, eliminating the feelineis of unsure and no-trust of resolubiliíy of life’s conditions and mainly, in the betterment of populations life quality.